Anti-hepatitis C virus activity and synergistic effect of Nymphaea alba extracts and bioactive constituents in liver infected cells. (August 2018) - Rehman, Sidra; Ashfaq, Usman Ali; Ijaz, Bushra; Riazuddin, Sheikh
Abstract: Background: Without an effective vaccine, hepatitis C virus (HCV) remains a global threat, inflicting 170–300 million carriers worldwide at risk of cirrhosis and hepatocellular carcinoma (HCC). Though various direct acting antivirals have been redeemed the hepatitis C treatment, a few restraints persist including possible side effects, viral resistance emergence, excessive cost which restricts its availability to a common person. Hypothesis: There is no preventive HCV vaccine available today so the discovery of potent antiviral natural flora and their bioactive constituents may help to develop preventive cures against HCV infection. Study design: In current study, we aim to clarify anti-HCV activity of methanol and acetone extracts along with the purified fractions of Pakistani local plant, Nymphaea alba L ( N. alba ) using Huh-7 cell line as transfection model. Synergistic study of purified fractions with interferon was performed using MDBK cell line (expressing interferon receptors) as transfection model. Materials and methods: Recent study by our research group has observed potent anti-HCV NS3 protease activity of methanol and acetone extracts of N. alba. Effect of N. alba extracts, its fractions precisely, the N1 and N8 fractions on HCV replication was demonstrated by analyzing viral gene expression using in vitro transfection model. Considering NS3 protease as a dynamic drug target, fourteen phytochemicals of N. alba were selected as ligands for interaction with NS3 protein using Molecular Operating Environment (MOE) software. Boceprevir, FDA approved NS3 protease inhibitor, was used as standard for comparative study in docking screening. Results: Herein we report 84% and 94% reduction of 3a genotype of HCV NS3/4A gene expression at mRNA level at non-toxic concentration. Specifically, two fractions ' N1 ' & ' N8 ' isolated from acetone extract suppressed HCV NS3 gene expression in transfected target cells with an EC50 value of 37 ± 0.03 μg/ml and 20 ± 0.02 μg/ml respectively. Similarly, viral genotype 1a replication is strongly suppressed in target cells by N. alba flower extracts and purified fractions. Moreover, combination of fractions with standard antiviral drug displayed synergistic effects for inhibition of HCV replication. Phytochemicals including Isoquercetin, Hyperoside, Quercetin, Reynoutrin, Apigenin and Isokaempferide displayed minimum binding energies as compared to standard protease inhibitor. Conclusion: N. alba and its purified phytochemicals with new scaffolds might significantly serve as valuable and alternative regimen against HCV either alone or in combination with other potential anti-HCV agents. Graphical abstract: Image 1 Highlights: Hepatocytes and fibroblasts cell treated with N. alba extract exhibited no cellular toxicity. N. alba extracts and partially purified fractions showed significant anti-HCV NS3 activity. N. alba inhibited substantial viral propagation in Huh-7 infected cells. N. alba phytochemicals showed least binding energies than boceprevir drug.